Cardioneuroablation eliminating cardiac asystole associated with area postrema syndrome: a case report and literature review - Wang, EnRun; Li, YuanJing; Yu, Gang; Liu, Gang; Deng, Jiang; Wang, YanFei; Yang, Wei; Chen, GuoDong; Zhu, Dennis W.; Jia, FengPeng (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThere have been few instances of symptomatic bradycardia-arrhythmia in the context of area postrema syndrome (APS), and some of them have been implanted permanent pacemakers. Cardioneuroablation (CNA) has emerged as a viable therapy for the treatment of syncope induced by neutrally mediated bradycardia or atrioventricular block.MethodsWe report a young patient with recurrent cardiac asystole and syncope following persistent hiccups caused by neuromyelitis optica spectrum disorder (NMOSD), who successfully completed CNA treatment and avoided permanent pacemaker placement. We also summarized and analyzed 20 previously reported cases that were relevant to APS with bradyarrhythmia.ResultsIn a patient with NMOSD, CNA can efficiently and safely eradicate symptomatic bradycardia-arrhythmia. A total of 21 cases were identified in the final analysis (including our case). The average age was 51 years old and female patients accounted for 38.1%. Brady-arrhythmia was presented in all patients, and 9 patients were implanted temporary or permanent pacemakers. 4 of the 9 patients were received permanent pacing therapy because they were not weaned off pacing support after etiological treatment.ConclusionsCardiac asystole and syncope after persistent hiccups may be the first signs of APS of medullary lesions, and CNA may be a useful therapy option for these patients in experienced centers. We believe that in this scenario, CNA may be a superior therapeutic option than permanent pacemaker placement. Additionally, the statement also serves as a cautionary reminder for health care professionals to establish an association between bradyarrhythmia and APS of medullary lesions in their clinical practice.